Modern Islamic Education in the Perspective of Seyyed Hossein Nasr and Its Relevance for the Development of Madrasah Teacher Professionalism - May Sarah (LP3M Pascasarjana STAI Ibnurusyd, 2026)
Modern Islamic education faces various challenges characterized by developments in science, technology, and globalization, which have impacted changes in the educational paradigm. In this context, the professionalism of madrasa teachers is a crucial aspect that needs to be developed to be able to meet the demands of the times without neglecting Islamic spiritual and moral values. This study aims to analyze the concept of modern Islamic education from the perspective of Seyyed Hossein Nasr and examine its relevance for the development of madrasa teacher professionalism. This study uses a qualitative approach with a library research type. Data were obtained from the works of Seyyed Hossein Nasr, books, scientific articles, and various relevant literature sources. Data analysis was conducted using content analysis techniques by identifying, classifying, and interpreting Nasr's ideas related to Islamic education. The results show that Islamic education according to Seyyed Hossein Nasr emphasizes the integration of intellectual, spiritual, and moral dimensions through the concept of the unity of knowledge and sacred knowledge. Nasr criticized modern education which tends to be secular and materialistic because it ignores the transcendental dimension in the educational process. This thinking is relevant to the development of madrasah teacher professionalism, particularly in strengthening pedagogical, professional, social, and personal competencies based on spiritual values. Thus, Seyyed Hossein Nasr's thinking can serve as a conceptual foundation for building madrasah teacher professionalism that not only excels academically but also possesses moral and spiritual integrity.